Artificial Intelligence (AI), the Erosion of Tacit Knowledge, and the Challenges of Cultivating Wisdom: Epistemological and Ethical Implications for 21st Century Islamic Education - Yazid Hady; Nofi Maria Krisnawati; Afsheen Fatima (Badan Litbang dan Diklat Kementerian Agama RI, 2025)
The integration of artificial intelligence (AI) into Islamic education offers efficiency and personalisation, but risks eroding tacit knowledge gained through experience, reflection, and spiritual relationships, which from the basis of wisdom and character building. This study uses a systematic literature review, utilising the Data–Information–Knowledge–Wisdom (DIKW) model and the tacit–explicit knowledge framework. The literature was obtained from academic databases (2020–2025) with strict inclusion and exclusion criteria. The findings show that AI is highly effective in disseminating explicit knowledge, but it cannot replace the vital role of tacit knowledge in nurturing students’ manners, wisdom, and spiritual values. Ethical challenges, algorithmic bias and dehumanisation, are increasingly pertinent in the digital era. The study emphasizes the need to position AI as a supportive tool, strengthen AI literacy rooted in Islamic values, and protect the role of teachers and human-oriented learning spaces to ensure that Islamic education remains rooted in humanity.